2010
DOI: 10.5194/angeo-28-1023-2010
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap convection/precipitation states during Earth passage of two ICMEs at solar minimum

Abstract: Abstract. We report important new aspects of polar cap convection and precipitation (dawn-dusk and inter-hemisphere asymmetries) associated with the different levels of The presence of a lobe cell and associated polar arcs in the Southern (summer) Hemisphere in the low density (1-2 cm −3 ) and B x =0 ICME case is accompanied by the dropout of polar rain precipitation in the dusk-side regime of sunward polar cap convection and inward-directed Birkeland current. The low-altitude observations are discussed in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…This demonstrates that flow channel FC 2 is formed by the ionospheric Pedersen current closure of Birkeland currents C1-C2. The C1-C2 Birkeland current configurations corresponding to the different FC 2 flow channels appearing during IMF B y < 0 conditions are indicated in Sandholt et al (2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that flow channel FC 2 is formed by the ionospheric Pedersen current closure of Birkeland currents C1-C2. The C1-C2 Birkeland current configurations corresponding to the different FC 2 flow channels appearing during IMF B y < 0 conditions are indicated in Sandholt et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Sandholt et al (2010) we reported one case showing the presence of a series of 5-10-min-long negative X-component magnetic deflections detected at ground stations located underneath the FC 2 flow channel of type NH-dusk/B y < 0. This led us to speculate that the ionospheric ion flow was also pulsed in this case and possibly related to flux transfer events (FTEs), i.e., momentum transfer in a later stage of the evolution of field lines previously opened by pulsed magnetopause reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…The dayside source is shown in the variant of negative IMF B y conditions (southwest-directed IMF) with E-field coupling along old open magnetic field lines (OOFLs), giving rise to a prenoon versus postnoon convection asymmetry (see e.g. Heppner and Maynard, 1987), i.e., E-field concentration in the postnoon sector via ionospheric Pedersen current closure of FACs marked R1-C1 (our FC 2 flow channel), as described by Sandholt and Farrugia (2009) and Sandholt et al (2010). The ground magnetic signature of this dayside convection source is demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crooker et al, 1991). For documentations of associations between auroral, magnetic and convection signatures of pulsed magnetopause reconnection in the postnoon sector we refer to Sandholt et al (1986), Sandholt and Farrugia (2007) and Sandholt et al (2010).…”
Section: P E Sandholt Et Al: Repetitive Substorm Activity Driven Bmentioning
confidence: 99%
“…Such channels of pulsed antisunward flows on old open field lines (polar rain precipitation) were documented by Sandholt and Farrugia (2009) and Sandholt et al (2010). Our aim here is to study the possible contribution of these flows to the CPCP fluctuations as measured by satellites in polar orbit or by ground-based radars.…”
Section: Electrojet Deflections: Ground Magnetometer Datamentioning
confidence: 99%